1997
DOI: 10.1046/j.1365-2249.1997.d01-1010.x
|View full text |Cite
|
Sign up to set email alerts
|

T helper responsiveness in human Loa loa infection; defective specific proliferation and cytokine production by CD4+ T cells from microfilaraemic subjects compared with amicrofilaraemics

Abstract: SUMMARYThe proliferation and cytokine profiles of peripheral blood mononuclear cells (PBMC) from microfilaraemic (Mf þ ) subjects infected by Loa loa in response to antigens of several parasitic stages were compared with those from amicrofilaraemic (Mf ¹ ) individuals. While a strong lymphoproliferative response and consistent levels of both Th1 (IL-2, interferon-gamma (IFN-g)) and Th2 (IL-4, IL-5) type cytokines were observed in response to adult worm (AW) and microfilariae (Mf) antigen in Mf ¹ individuals, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…12 In human loiasis, however, the same research group described significantly higher IL-10 production in amicrofilaremic than in microfilaremic subjects and concluded that this cytokine is not responsible for the Th unresponsiveness observed in the microfilaremic group. 14 The apparent divergences concerning the contribution of IL-10 to microfilaria-specific hyporesponsiveness can not be fully resolved by our data because we concentrated on analyses of cytokine production and T cell subpopulations and did not perform lymphoproliferation assays. In all, the expansion of the IL-10-producing lymphocyte subpopulation in our microfilaremic subjects did not significantly influence the frequency of Th1 cytokine-expressing cells represented by intracellular staining of IFN-␥, IL-2, and IFN-␥/IL-2.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…12 In human loiasis, however, the same research group described significantly higher IL-10 production in amicrofilaremic than in microfilaremic subjects and concluded that this cytokine is not responsible for the Th unresponsiveness observed in the microfilaremic group. 14 The apparent divergences concerning the contribution of IL-10 to microfilaria-specific hyporesponsiveness can not be fully resolved by our data because we concentrated on analyses of cytokine production and T cell subpopulations and did not perform lymphoproliferation assays. In all, the expansion of the IL-10-producing lymphocyte subpopulation in our microfilaremic subjects did not significantly influence the frequency of Th1 cytokine-expressing cells represented by intracellular staining of IFN-␥, IL-2, and IFN-␥/IL-2.…”
Section: Discussionmentioning
confidence: 91%
“…18 This finding has recently been substantiated in a study of human loiasis, which showed no differences between microfilaremic and amicrofilaremic individuals with respect to lymphoproliferation and cytokine production when PBMC were stimulated with nonspecific mitogens. 14 In addition, in a longitudinal study of L. loa-infected rhesus monkeys, blastogenic responses of PBMC and IL-2 production capacity decreased only after stimulation with filarial antigen. 13 By applying nonspecific (non-filarial) stimulants in our flow cytometric assay, it was nevertheless possible to elaborate differences between microfilaremic loiasis and the amicrofilaremic group, with an expansion of IL-4-, IL-10-, and IL-13-expressing CD4 ϩ cells within the microfilaremic individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…or phytohemagglutinin (PHA; 10 g/ml; Sepracor, Villeneuve-la-Garenne, France) as mitogen. For Ag, cells were stimulated with Mycobacterium tuberculosis purified protein derivative (PPD; 10 g/ ml, Statens Serum Institut, Copenhagen, Denmark), the parasite Ag L3 (2 g/ ml), adult worm (5 g/ml), or Mf Ag (10 g/ml), or medium alone, exactly as described previously (3). The plates were incubated at 37°C under an atmosphere of 5% CO 2 -air for 3 days (mitogen) or 5 days (Ag) and then pulsed with 1 Ci of [ 3 H]thymidine/well (Amersham, Les Ulis, France).…”
Section: Methodsmentioning
confidence: 99%
“…Culture supernatants were collected at 24 h (mitogens) and 48 h (Ag) for IL-2 and IL-4 determinations and at 96 h (antigens) for measurement of IL-5 and IFN-␥. Cytokine levels were measured by two-site enzyme-linked immunosorbent assay exactly as described previously (3). Results for IL-4 and IL-5 are expressed in picograms per milliliter and results for IL-2 are in units per milliliter, relative to human cytokine standards (R & D Systems, Abingdon, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%